Comparison of Success Rates of Biodentine and MTA Materials in Pulp Revascularization Treatment of Immature Permanent Teeth - Ramadhan, Raden Bryan Sukma; Cahyani, C; Ningsih, Juwita Raditya; Widyastuti, Noor Hafida (Universitas Muhammadiyah Surakarta, 2022)
Objective: To determine the success rate of biodentine and MTA materials in pulp revascularization treatment of immature permanent teeth.Methodology: The literature review approach was used in the research design, which was a means of gathering data from library sources. What performed data searches on Pubmed, ScienceDirect, and Google Scholar sites by specified keywords and filtered based on their association with the research title, inclusion, and exclusion criteria to ensure that publications fit the requirements.Results: Revascularization has been shown to be effective when performed on teeth with disinfected root canals, so it is important to obatain a good coronal seal. Coronal seal used biodentine is better than MTA. Biodentin has a better consistency, allows its condensation without apical displacement, and the short setting time allows the composite restoration to be placed simultaneously. Biodentin has the same mechanical properties as human dentin with very low cytotoxicity and can overcome the clinical drawbacks of MTA. Biodentine is tooth-colored and does not cause discoloration.Application/Originality/Value: Literature review contributes to comparing Success Rates of Biodentine and MTA Materials to increase knowledge and success in Immature Permanent Dental Pulp Revascularization Treatment. The results obtained are better because the literature review of this study compares several journals with different research objects, research samples, methods, and results.